(untitled) (Revista Contexto & Saúde, 2026)
Objective: To determine the incidence of delirium in critically ill users admitted to the intensive care unit (ICU) and analyze its association with clinical and therapeutic variables using the Confusion Assessment Method for the Intensive Care Unit (CAM-ICU). Methods: This prospective, analytical, observational study included 108 adult ICU users. Data were collected using clinical forms and the CAM-ICU tool, administered by trained physiotherapists. The investigated variables included sex, age, length of hospitalization, type of admission, sedation, mechanical ventilation, and the occurrence of delirium. Associations were tested using the chi-square test at a significance level of 5 %. Results: Delirium was identified in 29.6% of users. A statistically significant association was found between delirium and the use of sedation (P = 0.010) and mechanical ventilation (P < 0.001). Users receiving mechanical ventilation were 5.65 times more likely to develop delirium, and those diagnosed with delirium had longer hospital stays. Conclusion: Sedation and mechanical ventilation were significantly associated with delirium in critically ill users. These findings reinforce the need for preventive measures, routine delirium monitoring, and multidisciplinary management strategies to minimize adverse outcomes during ICU stays.